2002
DOI: 10.1016/s0002-9440(10)64485-9
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the EP2 Prostaglandin E2 Receptor in Immortalized Human Keratinocytes Results in Increased Invasiveness and Decreased Paxillin Expression

Abstract: Prostaglandin E(2) (PGE(2)) receptor subtype EP(2), which is coupled to cAMP metabolism, is known to mediate proliferation of primary human keratinocytes in vitro. The effect of gain or loss of EP(2) receptors in immortalized human keratinocytes (HaCat cells) was examined. HaCat keratinocytes were transfected with sense or anti-sense constructs of the EP(2) receptor. Loss or gain of EP(2) expression was documented by immunoblot and associated changes in agonist-stimulated cAMP production. Loss or gain of EP(2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…Konger et al 24 found that a decrease in the number of EP2 receptors resulted in a lack of adhesion, and conversely, an increase in EP2 receptor numbers promoted cell adhesion in immortalized human keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Konger et al 24 found that a decrease in the number of EP2 receptors resulted in a lack of adhesion, and conversely, an increase in EP2 receptor numbers promoted cell adhesion in immortalized human keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors arising in EP2À/À mice contain fewer CD31 + cells and more evidence of apoptosis, suggesting that PGE 2 -mediated signaling through EP2 drives tumor angiogenesis and apoptosis resistance. In direct contrast, however, loss of EP2 in immortalized keratinocytes was associated with increased invasiveness (20). Also unresolved is the role of EP3.…”
Section: Ep Expression and Function In Cancer Is Complexmentioning
confidence: 97%
“…33 In contrast, Konger et al reported that loss of EP 2 receptor in immortalised human keratinocytes resulted in increased invasiveness. 50 They suggested that this discrepancy may be caused by differences in cell or tissue type, and the presence of negative feedback loop.…”
Section: Discussionmentioning
confidence: 99%